Light Intensity Effects on Productivity and Post-Harvest Quality in Perilla frutescens Cultivated in CEA - Akvilė Viršilė; Ieva Gudžinskaitė; Kristina Laužikė; Gediminas Kudirka; Audrius Pukalskas; Giedrė Samuolienė (Agriculture)
Leafy vegetables, mainly lettuces, are currently the main crop cultivated in controlled environment agriculture (CEA), including vertical farming and plant factories. There is a rising demand to expand this portfolio with a wider variety of underutilized edible plants containing various bioactive compounds and sensory properties seeking to enrich human diets. However, the optimal cultivation conditions for these underutilized plants significantly differ from those optimized for lettuce, basil, and other popular CEA crops. Therefore, this study aims to explore the impacts of light-emitting diode (LED) lighting intensity (photosynthetic photon flux density, PPFD) on green leaf Perilla frutescens cultivated in CEA. Plants were grown under four levels of LED lighting PPFDs from 150 to 300 µmol m−2s−1 for 4 weeks. Plant biomass productivity, soluble sugar contents, antioxidant properties (DPPH, ABTS free radical scavenging activities, FRAP antioxidant power), and total contents of phenolic compounds in leaves were evaluated at harvesting time. Further, harvested plant material was stored in the dark, at +6 °C, and the water content, water loss and transpiration rate, leaf sugar contents, and antioxidant properties were monitored 1, 3, and 5 days after harvesting. The summarized data suggest that higher cultivation lighting PPFD results in better harvest quality preservation during post-harvest storage.